NIAT BERKUNJUNG KEMBALI DI RESTORAN LIKA LIKU DITINJAU DARI HARGA DAN KEPUASAN PELANGGAN - Vardhani, Nadia; Octafian, Ray (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The competitive restaurant industry demands strategies to attract and retain customers. This research aims to analyze the influence of price and customer satisfaction on intention to revisit a restaurant. This research uses quantitative methods with a survey design. Data was collected from 100 respondents who had visited the restaurant. Data were analyzed using path analysis. The results show that price and customer satisfaction have a positive and significant influence on intention to revisit, satisfaction mediates the effect of price on intention to revisit. In conclusion, price and customer satisfaction are important factors in increasing intention to visit again. Restaurants need to pay attention to pricing strategies and increasing customer satisfaction to attract and retain customers.